The Impact of Multifaceted Osteoporosis Group Education on Patients’ Decision-Making regarding Treatment Options and Lifestyle Changes - Jensen, Annesofie L.; Wind, Gitte; Langdahl, Bente Lomholt; Lomborg, Kirsten (Journal of Osteoporosis, 2018)
Introduction. Patients with chronic diseases like osteoporosis constantly have to make decisions related to their disease. Multifaceted osteoporosis group education (GE) may support patients’ decision-making. This study investigated multifaceted osteoporosis GE focusing on the impact of GE on patients’ decision-making related to treatment options and lifestyle. Material and Methods. An interpretive description design using ethnographic methods was utilized with 14 women and three men diagnosed with osteoporosis who attended multifaceted GE. Data consisted of participant observation during GE and individual interviews. Results. Attending GE had an impact on the patients’ decision-making in all educational themes. Patients decided on new ways to manage osteoporosis and made decisions regarding bone health and how to implement a lifestyle ensuring bone health. During GE, teachers and patients shared evidence-based knowledge and personal experiences and preferences, respectively, leading to a two-way exchange of information and deliberation about recommendations. Though teachers and patients explored the implications of the decisions and shared their preferences, teachers stressed that the patients ultimately had to make the decision. Teachers therefore refrained from participating in the final step of the decision-making process. Conclusion. Attending GE has an impact on the patients’ decision-making as it can initiate patient reflection and support decision-making.